Social presence in online learning communities: the role of personal profiles - Karen Kear; Frances Chetwynd; Helen Jefferis (Association for Learning Technology, 2014)
Online communication is increasingly used in education, but it is not without problems. One significant difficulty is a lack of social presence. Social presence relates to the need for users of technology-based communication to perceive each other as real people. Low social presence can be a particular issue in text-based, asynchronous systems such as discussion forums, leading to feelings of impersonality and disengagement from online learning. Features of online communication systems have the potential to increase social presence. One possibility, advocated in the literature on online learning, is the use of personal profiles and photos to help participants to learn something about each other and feel more connected. This paper discusses the question: To what extent do personal profiles enhance social presence in online learning communities? It presents research findings from two studies which investigated learners' use and perceptions of personal profiles in online forums. The findings suggest that personal profiles and photos help some online learners to feel in touch with each other. Other learners, however, do not feel the need for these facilities, have privacy concerns or prefer to focus on the forum postings.